2016
DOI: 10.1159/000449384
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of True Uterine Artery Aneurysms Diagnosed during Pregnancy

Abstract: We report 2 cases of true uterine artery aneurysms diagnosed during pregnancy. Both cases presented with nonspecific symptoms such as urethral obstruction, minimal vaginal bleeding and lower abdominal pain in the 2nd trimester. Both aneurysms were diagnosed by color Doppler ultrasound. In the first case labor was induced at 37 + 4 weeks of gestation. However, due to sudden fetal distress and maternal abdominal pain, an emergency Caesarean section was performed during labor, and 3 liters of intra-peritoneal blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A UAP may be asymptomatic but usually presents with secondary postpartum hemorrhage (PPH) or delayed vaginal bleeding. 9 Some authors have indicated that UAP is a rare and potentially life-threatening lesion. 4 They described its mechanism as blood flowing into periarterial tissues after a wall defect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A UAP may be asymptomatic but usually presents with secondary postpartum hemorrhage (PPH) or delayed vaginal bleeding. 9 Some authors have indicated that UAP is a rare and potentially life-threatening lesion. 4 They described its mechanism as blood flowing into periarterial tissues after a wall defect.…”
Section: Discussionmentioning
confidence: 99%
“…A UAP may be asymptomatic but usually presents with secondary postpartum hemorrhage (PPH) or delayed vaginal bleeding. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-traumatic, spontaneous non-scarred uterine ruptures during childbirth are significantly less common than traumatic ones, and are associated with uterotonic stimulation or hyperstimulation, multiparity, protracted or precipitated childbirth, fetal malpresentation, and previous uterine instrumental procedures [1,2]. The most common site of rupture, locus minoris resistentiae, is the isthmic part of the uterus, which is the transition from the contraction to the distraction part of the uterus where the anatomical connection to the uterine vascular parametric plexus is located.…”
Section: Commentarymentioning
confidence: 99%
“…The most common site of rupture, locus minoris resistentiae, is the isthmic part of the uterus, which is the transition from the contraction to the distraction part of the uterus where the anatomical connection to the uterine vascular parametric plexus is located. A rupture there causes a rupture of the ascending or descending arm of the uterine artery with the development of massive intra-or retroperitoneal hemorrhage [1][2][3]. In addition to the listed possible causes, vascular anomalies, such as uterine artery or arteriovenous aneurysms, which change the vasculature and histoarchitectonics of the juxtaisthmic uterine part, are also mentioned as very rare causes.…”
Section: Commentarymentioning
confidence: 99%